The development and performance trends in Olympic track and field: 1972 - 2008 - Tilinger, P.; Kovar, K. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The Olympic Games are multi sport and multi cultural event, which takes place on a regular basis at different locations. Because the Olympic Games represent the highest level of competition, particularly in track and field, they became the largest international sport event for competitors as well as spectators. For the past few years we have analyzed the performance trends in sport as a basis for prediction of future development. We believe that the prediction of future performances is a very important tool for management and leadership in the area of sport training and competition (Wazny, 1981; Digel, 1995; Pfützner, 2001). Methods Olympic Track and Field events were analyzed from 1972 to 2000 in performance trends, relationship between politics and sport, development of organizational structures, rules development, trends in sport training, development of technique, development of equipment and material support for Track and Field. The research methods included statistical analysis of performances at Olympic Games, analysis of literature, interviews and questionnaires administered to athletes and coaches. Results The long-term research in the Olympic track and field makes it possible to predict the level of performances, which may be expected in future years. (Table 1) Common characteristics for all disciplines: - sharp increments in performance before 1988 was somewhat affected by the Olympic boycott in 1980 and 1984; - minimal or no increments in performance during the nineties; - each discipline has its own star who contributed to a substantial advancement of performance (Grifit, Lewis, Johnson, African middle and long distance runners etc.) Discussion/Conclusions The results of our study suggest that sport will continue to play a very important role in publicity and promotion of overall development of many countries. The performance levels will continue to grow because of the development of new knowledge, which contributes to a higher quality of practice, improvement of technique, and above all, because of improved material support for athletics. The coaches and athletes believe that the trend toward increase frequency of competition among the top world athletes will continue because of its attractiveness for sponsors and media.